A Portrait of Non-Tenure-Track Faculty in Technical and Professional Communication: Results of a Pilot Study. (April 2016) - Meloncon, Lisa; England, Peter; Ilyasova, Alex
We report the results of a pilot study that offers the field of technical and professional communication its first look at material working conditions of contingent faculty, such as course loads, compensation, and professional support. Findings include that contingent faculty are more enduring with stable full-time, multi-year contracts; they carry a substantial teaching loads; and the majority are satisfied and happy in their present position, but half would prefer to be working on the tenure track.